Automatic balancing mechanisms for notional defined contribution accounts in the presence of uncertainty. Issue 2 (7th February 2018) - Alonso-García, Jennifer; Boado-Penas, María del Carmen; Devolder, Pierre
Abstract : The notional defined contribution model combines pay-as-you-go financing and a defined contribution pension formula. This paper aims to demonstrate the extent to which liquidity and solvency indicators are affected by fluctuations in economic and demographic conditions and to explore the introduction of an automatic balancing mechanism (ABM) into the pension scheme. We demonstrate that the introduction of an ABM reduces the volatility of the buffer fund and that, in most cases, the automatic mechanism that re-establishes solvency produces the highest value of the risk-adjusted notional factor.